Prosthetic rehabilitation of a child with Rubinstein-Taybi Syndrome after dental trauma: case report - Sarah Katherine de Oliveira SILVA; Nilton Cesar Nogueira dos SANTOS; Francisco Xavier Paranhos Coêlho SIMÕES; Ana Carolina Del-Sarto Azevedo MAIA (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Rubinstein Taybi syndrome has a genetic origin in the chromosome 16. It has physical characteristics, delay in physical and mental development, and may present oral alterations. This paper aims to report a case of prosthetic rehabilitation of a patient with syndrome who, due to dental trauma, lost dental elements early. Female patient, 4 years and 7 months old, with loss of the deciduous maxillary central incisors. The data collection was carried out through anamnesis, clinical and complementary exams. After the diagnosis and the establishment of the treatment plan, we made a Denari type prosthesis. It has a tube-bar mechanism that allows maxillary growth and development. At the end of treatment, the caregiver was instructed to make periodic visits to the dentist for clinical and radiographic follow-up of the prosthesis, as well as the need for treatment with the speech therapist. The loss of anterior deciduous teeth can be associated with trauma in this region and the dental absence can affect the development and behavior of children, promoting a change in daily life and impacting the quality of life of the whole family. The Denari prosthesis is a viable treatment option for children with this syndrome, as it accompanies the maxillary growth, restores the functions of the stomatognathic system, prevents deleterious oral habits and helps with phonetics. It is necessary for the dentist to be able to offer the best treatment for these patients, as the syndrome makes it difficult, but does not impede its execution.